Authorized self-study guide : Cisco IP Telephony (CIPT) - Cioara, Jeremy (Certification self-study series, 2006)
Foundation Learning for CCVP IP Telephony Jeremy Cioara, CCIE® No. 11,727 Cisco IP Telephony (CIPT), Second Edition, is a Cisco®-authorized, self-paced learning tool for CCVP IP telephony foundation learning. This book provides you with the knowledge needed to install, configure, and maintain a Cisco IP telephony solution. By reading this book, you will gain a thorough understanding of Cisco Unified CallManager version 4.1, the call routing and signaling component for the Cisco IP telephony solution. Cisco IP Telephony (CIPT) expands your knowledge of voice over IP (VoIP) and public switched telephone network (PSTN) components and technologies. This book teaches you how to describe, install, configure, and support Cisco Unified CallManager 4.1 in a Cisco network including such features as security and video; how to configure gateways, gatekeepers, and switches; and how to build route plans to place intra- and intercluster Cisco IP phone calls. Chapter review questions, detailed configuration examples, network diagrams, and thorough explanations help reinforce learning. Whether you are preparing for CCVP certification or simply want to gain a better understanding of IP telephony and Cisco Unified CallManager, you will benefit from the foundation information presented in this book. Cisco IP Telephony (CIPT), Second Edition, is part of a recommended learning path from Cisco Systems® that includes simulation and hands-on training from authorized Cisco Learning Partners and self-study products from Cisco Press. To find out more about instructor-led training, e-learning, and hands-on instruction offered by authorized Cisco Learning Partners worldwide, please visit www.cisco.com/go/authorizedtraining. Jeremy D. Cioara, CCIE® No. 11,727, is the owner of AdTEC Networks and works as a network consultant, instructor, and author. He has been working in network technologies for more than a decade and has deployed networks worldwide. His current consulting work focuses on network and VoIP implementations. Examine design strategies behind a Cisco Unified CallManager cluster, cluster replication, and Cisco Unified CallManager deployment models Perform Cisco Unified CallManager server installations and upgrades Learn the features of all Cisco IP Phones, the IP phone startup process, and audio codec communication Add IP phone users and apply bulk moves, adds, and changes Configure Cisco gateways and trunks Design and configure Cisco Unified CallManager route ...